Evaluating the strength, durability and porosity characteristics of alluvial clay stabilized with marble dust as a sustainable binder - Mohamad Hanafi; Israf Javed; Abdullah Ekinci (Results in Engineering)
High-plasticity soils such as alluvial clay deform easily under heavy loads due to their strong plastic behavior. The tendency of these soils to expand and contract can cause deformation and cracking in structures, posing challenges in construction. To address these challenges, it's essential to improve these soils to enhance their strength and reduce plasticity before construction. Therefore, this study aims to evaluate the applicability of marble dust as a sustainable alternative to Portland cement in ground improvement applications, specifically to improve the behavior of alluvial clay. The performance of marble dust, Portland cement, and alluvial clay mixtures was evaluated using unconfined compressive strength (UCS), shear wave velocity, and mass loss due to weathering. The study tested three Portland cement contents (7, 10, and 13 %), two dry density (1.6 and 1.8 g/cm3), and two marble dust contents (0, 10 and 20 %) across three curing ages (7, 28, and 60 days). Microstructural analysis was performed using SEM. Results indicated a slight decrease in 7-day strength (up to 8.3 %) with 10 % marble dust replacement due to minimal pozzolanic activity, while 28-day strength loss was less significant. On the other hand, the 60-day strength increased up to 20 % upon replacing 10 % of cement with marble dust. The marble dust addition also increased the shear modulus of the soil by up to 9 % when compared with cement only. The adjusted porosity index of 0.32 correlated unconfined compressive strength (qu), initial shear modulus (G0), and accumulated loss of mass (ALM) across varying densities and blend proportions. ALM increased linearly with wet-dry cycles, with higher compaction and binder content reducing mass loss per cycle. More marble dust, however, led to greater mass loss at both curing ages, attributed to reduced cement content.